Indonesian Trade Balance Performance By GDP, Exports, Imports, BI Rate and Inflation as Intervening Variables - Riska Ektiarnanti; Anis Rahmawati; Feni Krismawati Fauziah; Isma'iddatur Rofiqoh (Cahaya Abadi Publisher, 2023)
The performance of international trade in Indonesia has fluctuated for several years, volatile inflation has a positive or negative impact on GDP results, imports and exports which are indicators of the trade balance and the BI Rate as an inflation controller affect the trade balance performance policy. The research approach is monthly data for a 5-year period, secondary data using path analysis techniques. The findings of this study indicate that GDP indirectly through inflation affects the trade balance, directly exports through inflation has no effect on the trade balance, directly imports through inflation has a significant effect on the trade balance, indirectly the BI Rate has a significant effect on the trade balance, inflation has a significant effect on the trade balance.